Niche Partitioning of the N Cycling Microbial Community of an Offshore Oxygen Deficient Zone - Fuchsman, Clara A.; Devol, Allan H.; Saunders, Jaclyn K.; McKay, Cedar; Rocap, Gabrielle (Frontiers in Microbiology, 2017)
Microbial communities in marine oxygen deficient zones (ODZs) are responsible for up to half of marine N loss through conversion of nutrients to N2O and N2. This N loss is accomplished by a consortium of diverse microbes, many of which remain uncultured. Here, we characterize genes for all steps in the anoxic N cycle in metagenomes from the water column and >30 μm particles from the Eastern Tropical North Pacific (ETNP) ODZ. We use an approach that allows for both phylogenetic identification and semi-quantitative assessment of gene abundances from individual organisms, and place these results in context of chemical measurements and rate data from the same location. Denitrification genes were enriched in >30 µm particles, even in the oxycline, while anammox bacteria were not abundant on particles. Many steps in denitrification were encoded by multiple phylotypes with different distributions. Notably three N2O reductases (nosZ), each with no cultured relative, inhabited distinct niches; one was free-living, one dominant on particles and one had a C terminal extension found in autotrophic S-oxidizing bacteria. At some depths >30% of the community possessed nitrite reductase nirK. A nirK OTU linked to SAR11 explained much of this abundance. The only bacterial gene found for NO reduction to N2O in the ODZ was a form of qnorB related to the previously postulated “nitric oxide dismutase,” hypothesized to produce N2 directly while oxidizing methane. However similar qnorB-like genes are also found in the published genomes of many bacteria that do not oxidize methane, and here the qnorB-like genes did not correlate with the presence of methane oxidation genes. Correlations with N2O concentrations indicate that these qnorB-like genes likely facilitate NO reduction to N2O in the ODZ. In the oxycline, qnorB-like genes were not detected in the water column, and estimated N2O production rates from ammonia oxidation were insufficient to support the observed oxycline N2O maximum. However both qnorB-like and nosZ genes were present within particles in the oxycline, suggesting a particulate source of N2O and N2. Together, our analyses provide a holistic view of the diverse players in the low oxygen nitrogen cycle.